Wombs with a view : illustrations of the gravid uterus from the Renaissance through the nineteenth century /: illustrations of the gravid uterus from the Renaissance through the nineteenth century. (2016) - Longo, Lawrence D; Reynolds, L. P (Lawrence P.)
No abstract available